2019
DOI: 10.1088/1741-4326/ab076d
|View full text |Cite
|
Sign up to set email alerts
|

L-mode-edge negative triangularity tokamak reactor

Abstract: The negative triangularity tokamak (NTT) is a unique reactor concept based on "powerhandling-first" philosophy with the heat exhaust problem as the leading concern. The present paper exposes a reactor concept using L-mode edge based on negative triangularity tokamak (NTT) configuration, providing merits of no (or very weak) ELMs, larger particle flux and large major radius for power handling. It is shown that a reasonably compact (R p from 9m to 7m) NTT reactor is possible by achieving higher confinement impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 57 publications
(86 reference statements)
2
54
0
1
Order By: Relevance
“…While week (grassy) H-mode operation may still be possible in the 1 st stability region, high power discharges with δ 0 are predicted to operate near the 1 st instability boundary, which will limit the maximum pedestal gradient to significantly depressed values compared to traditional H-mode operation. Further experimental and modeling studies are needed to understand if the prominent infinite-n ballooning modes predicted by this work are benign at reactor scales, as has been suggested by previous work [9,11].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…While week (grassy) H-mode operation may still be possible in the 1 st stability region, high power discharges with δ 0 are predicted to operate near the 1 st instability boundary, which will limit the maximum pedestal gradient to significantly depressed values compared to traditional H-mode operation. Further experimental and modeling studies are needed to understand if the prominent infinite-n ballooning modes predicted by this work are benign at reactor scales, as has been suggested by previous work [9,11].…”
Section: Discussionmentioning
confidence: 73%
“…Looking forward towards development of tokamak reactors, these results suggest that NT could be an important and robust mechanism with which to reduce the height of the pressure pedestal and completely eliminate or severely mitigate dangerous instabilities like ELMs [9,11,15]. Additionally, if L-mode operation is desired, these results suggest that discharges with exceptionally high squareness (which also maximizes plasma volume) could also provide an attractive alternative to the traditional "Dee" shape.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…NT has been investigated as a means to suppress trapped electron mode turbulence dominated in TCV [96,97,98,99,100], however, recent modeling using nonlinear gyrokinetics [101,102,103] and further experimental results on TCV and DIII-D [104,105,106,107] have shown that NT may also suppress ITG turbulence in reactorrelevant regimes. Furthermore, diverted NT discharges [108,107] with low field strike points at large major radius are anticipated to have easier divertor engineering [109,110,108]. NT also helps preserve L-mode by greatly increasing the H-mode power threshold, sometimes even eliminating the L-H transition entirely [106,104,108,107].…”
Section: Extrapolation To Negative Triangularitymentioning
confidence: 99%
“…good power handling and boundary control [3]. Hence, plasma relaxation must be addressed in a base state which is either three dimensional or even stochastic.…”
mentioning
confidence: 99%